(untitled) (Research, Society and Development, 2020)
The study of spatial distribution is important for the elaboration of plans to help in the monitoring, prevention and control of pests in areas of agricultural crops. The scientific objectives highlight the advantages of assessing the spatial distribution of pests, including the use of geostatistics as a fundamental aid for the analysis and development of the integrated management plan. For the Praelongorthezia praelonga scale insects , tests were conducted in two commercial citrus growing areas, one of 58,240 m2 of agroforestry and another of 49,280 m2 of conventional type, both located in Capitão Poço, PA. The collections were carried out from September 2008 to August 2009 in all plants in the areas, evaluating the occurrence of nymphs and / or live adults of P. praelonga. Monthly evaluations were carried out observing the presence or absence of the pest in both cultivation systems. The areas were georeferenced and spatial analysis was performed using semivariogram models and interpolation of kriging maps. The best fit model for the data was exponential, with ranges ranging from 3.8 to 5.8 m for the conventional system and 3.3 to 7.3 m for the agroforestry system. Kriging maps showed the spatial distribution of the pest in the studied areas, indicating strong aggregation in both systems with Spatial Dependence Index (IDE) with values ​​between 0 to 0.605 ranging from strong to moderate for all evaluations in two the cultivation areas.